The Impact of Tiktok Social Media on the Behavior of Elementary School Students - Firdausia, Salsabila; Dafit, Febrina (Graduate Program Magister Manajemen Pendidikan, 2025)
The rapid development of social media, especially tiktok, offers entertainment for its users. Although tiktok offers entertainment, too intensive use can affect the behavior of its users, including elementary school students to their user behavior, and elementary school students are no exception. The purpose of this study is to identify and analyze the impact of tiktok use on fourth grade students of SD Miftahul Iman, both in terms of positve and negative. The research method used is a qualitative narrative approach through observation, interviews, and documentation to students, teachers, and parents. The data analysis techniques used include data reduction, presenting it, and drawing conclusions interactively and repeatedly to understand patterns in social phenomena. The results of the study show that tiktok has a positive and negative impact on student behavior. The positive impact includes honing skills and skills (e.g. Creativity in creating content). However, there are also significant negative impacts, including a lack of social care for students in the home and school environment, waste of time, and exposure to age-inappropriate content. The implication of this study is the importance of more intensive supervision and education from schools and parents regarding the use of social media in elementary school-age children to minimize negative impacts and optimize their positive potential.